2022
DOI: 10.1111/ffe.13652
|View full text |Cite
|
Sign up to set email alerts
|

On the static and fatigue life of nano‐reinforced Al‐GFRP bonded joints under different dispersion treatments

Abstract: As bonded components of engineering structures inevitably experience fatigue loading conditions during their service life, it is significant to find ways to enhance their endurance. Also, adding nanoparticles to the adhesive can be introduced as an approach to design more durable bonded joints. In this way, it is important to determine a nanoparticle dispersion method which can lead to the longest fatigue life. Accordingly, this paper aims to investigate the influence of various nanoparticle dispersion treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…After sonication, the dispersion was poured into the epoxy resin and agitated at 800 rpm for about 30 min to ensure homogeneity in the dispersed mixture. According to earlier researches, 42,43 adding acetone to the resin nanoparticle mixture and then subjecting it to a sonication procedure resulted in a noticeable increase in the mechanical properties. However, the amount of epoxy used for the current investigation was comparatively larger.…”
Section: Fabrication Of Compositesmentioning
confidence: 99%
“…After sonication, the dispersion was poured into the epoxy resin and agitated at 800 rpm for about 30 min to ensure homogeneity in the dispersed mixture. According to earlier researches, 42,43 adding acetone to the resin nanoparticle mixture and then subjecting it to a sonication procedure resulted in a noticeable increase in the mechanical properties. However, the amount of epoxy used for the current investigation was comparatively larger.…”
Section: Fabrication Of Compositesmentioning
confidence: 99%
“…The morphology of HNTs shown in Figure 7 depicts the crack‐pinning effect involving the creation of such a network of obstacles that impedes the propagation of cracks in the matrix. The reinforcement effect involves adding strength and stiffness to the matrix through the incorporation of high‐strength and high‐aspect ratios of nanofillers 66–68 . These mechanisms make epoxy composites with nanotubes better suited for high‐stress applications such as aerospace, automotive, and maritime industries.…”
Section: Resultsmentioning
confidence: 99%
“…The reinforcement effect involves adding strength and stiffness to the matrix through the incorporation of high-strength and high-aspect ratios of nanofillers. [66][67][68] These mechanisms make epoxy composites with nanotubes better suited for high-stress applications such as aerospace, automotive, and maritime industries. Figure 8 shows peculiar features of HNTs, showing a hollow lumen (Figure 8A), which is capable to carry epoxy resin into the lumen and thus exhibits efficient stress transfer in the composites, as corroborated by our previous study.…”
Section: Fracture Featuresmentioning
confidence: 99%
“…It is seen in Figure 3(e) and (f) that the weight percentage of boron compounds increases from 3 to 5 wt%, causing more agglomeration of boron compounds. Zamani et al 31 reported that the addition of more hybrid weight content increases the size of agglomerated particles in the composite. While the high surface area/volume ratio of the particle boron fillers enhanced the YM and FM, a little agglomeration in the composite structure caused a reduction of about 11–12% in the tensile and flexural strengths.…”
Section: Resultsmentioning
confidence: 99%